Grenada, West Indies - Perspectives for the development of educational programmes 1974-1983 - Fernando, W. D. (Ministry of Education, 1974)
This study sought to: 1) evaluate the educational priorities of Grenada in relation to the socioeconomic needs and the educational policy of the government, 2) provide direction on modern techniques of educational planning, and 3) provide guidelines for the development of education during the decade 1974-1983. Data were collected through a questionnaire to parents and students; discussions with ministry officials, principals, teachers, parents, and students; and visits to a number of schools and other educational institutions
Keywords: Educational development